GLOBAL EPIDEMIOLOGICAL SITUATION AND NEW IMMUNISATION ASPECTS - L.S. Namazova-Baranova; A.A. Baranov; D. McIntosh (Педиатрическая фармакология)
Results of numerous international epidemiological studies currently suggest a growing prevalence of many infectious diseases and, hence, an increased number of complications and fatal outcomes. The global medical community has come to a conclusion about the need to use all available efficient and safe vaccines in order to fight the spread of infections that cannot be tolerated in modern society (pertussis, poliomyelitis, measles, rubella, etc.) The article provides the latest data on these infections, their prevalence, and international recommendations on immunisation against influenza, which is especially critical in the light of recent H1N1 influenza pandemic and its likely propagation going forward as the virus continues to mutate. Key words: controlled infectious diseases, epidemiology, vaccination, children. (Pediatric Pharmacology. – 2010; 7(6):6-9)